Design Elements Affecting the Using of Atriums in Shopping Malls in Erbil city - Ali, Lana Abubakr; Ali, Ansam Salih; Muhammad, Shna Asaad (Sulaimani Journal for Engineering Sciences, 2017)
Open space represent one of the most important aspects of urban environment which affects our life each single day and usually people have a good relation with them, and as there are an outdoor open spaces there are also inner ones that usually people involve with it most of time, Atriums represents one of these spaces which consider large covered central courtyard acts as an attraction area where humans interact & communicate with each other as gathering place ,relaxing ,galleries and exhibitions. Shopping malls owns such spaces which acts effectively when it described in two ideas; business success and architectural success. The research will focus on the architectural success by specifying the occupational efficiency of atriums, although previous literatures covered many architectural aspects of these atriums but, the research noticed weakness in the relation between architectural design factors and users in atrium, regarding physical factors and occupational efficiency which declare as a density of using atriums in Malls that have been explained in two parts (Theoretical and Practical).the research focus on analyzing five malls in Erbil city.
Keywords: Atrium; Design Factors; Occupational-Efficiency; Shopping Malls; Users